Between Black Knives and Blessing Puffs: Traditional Healings in Georgia - Norsa, Alessandro; Varshalomidze, Gubazi (Uniwersytet Wrocławski. Centrum Interdyscyplinarnych Badań Relacji między Kulturą Oralną i Piśmienniczą, 2022)
The magic practices that we will meet during the following pages refer to the mountain areas of Agiara (independent region of Georgia). The focus of the research consisted in investigating the magical dimension still present in the Georgian population. The interviews that are the essence of this work were carried out in a research campaign and were essentially concentrated in two very distinct realities: Batumi and the countryside of Xelvachauri which is eleven kilometres from the city. In the following pages we will analyze the complex systems of interaction between magic, society and religion. We are happy to be able to bring these revelations because untill now, no in-depth studies had been made in this area regarding this issue.
Keywords: anthropology; magic; Georgia; blessing blow; healer